Gene expression alterations of human liver cancer cells following borax exposure - Wu, Lun; Wei, Ying; Zhou, Wen‑Bo; Zhang, You‑Shun; Chen, Qin‑Hua; Liu, Ming‑Xing; Zhu, Zheng‑Peng; Zhou, Jiao; Yang, Li‑Hua; Wang, Hong‑Mei; Wei, Guang‑Min; Wang, Sheng; et al. (Oncology reports, 2019)
Borax is a boron compound that is becoming widely recognized for its biological effects, including lipid peroxidation, cytotoxicity, genotoxicity, antioxidant activity and potential therapeutic benefits. However, it remains unknown whether exposure of human liver cancer (HepG2) cells to borax affects the gene expression of these cells. HepG2 cells were treated with 4 mM borax for either 2 or 24 h. Gene expression analysis was performed using Affymetrix GeneChip Human Gene 2.0 ST Arrays, which was followed by gene ontology analysis and pathway analysis. The clustering result was validated using reverse transcription‑quantitative polymerase chain reaction. A cell proliferation assay was performed using Celigo Image Cytometer Instrumentation. Following this, 2‑ or 24‑h exposure to borax significantly altered the expression level of a number of genes in HepG2 cells, specifically 530 genes (384 upregulated and 146 downregulated) or 1,763 genes (1,044 upregulated and 719 downregulated) compared with the control group, respectively (≥2‑fold; P<0.05). Twenty downregulated genes were abundantly expressed in HepG2 cells under normal conditions. Furthermore, the growth of HepG2 cells was inhibited through the downregulation of PRUNE1, NBPF1, PPcaspase‑1, UPF2 and MBTPS1 (≥1.5‑fold, P<0.05). The dysregulated genes potentially serve important roles in various biological processes, including the inflammation response, stress response, cellular growth, proliferation, apoptosis and tumorigenesis/oncolysis.